One-Pot Synthesis of Benzochromene Derivatives Catalyzed by KF-Al2O3 with Grinding - Jin, Tong-Shou; Xie, Hong; Xue, Yu-Peng; Li, Tong-Shuang (Asian Journal of Chemistry, 2010)
An efficient and convenient approach to the condensation reaction of naphthol, aromatic aldehydes and malono-nitrile using KF-Al2O3 as catalyst with grinding at room temperature (without any solvent) is described. This method provides several advantages such as neutral condition, simple work-up procedure, high yields and reduced environmental impact.